Preservation of high‐P rocks coupled to rock composition and the absence of metamorphic fluids. (7th February 2019) - Skelton, Alasdair; Peillod, Alexandre; Glodny, Johannes; Klonowska, Iwona; Månbro, Carolina; Lodin, Karin; Ring, Uwe
Abstract: Eclogites, blueschists and greenschists are found in close proximity to one another along a 1‐km coastal section where the Cyclades Blueschist Unit (CBU) is exposed on SE Syros, Greece. Here, we show that the eclogites and blueschists experienced the same metamorphic history: prograde lawsonite blueschist facies metamorphism at 1.2–1.9 GPa and 410–530°C followed, at 43–38 Ma, by peak blueschist/eclogite facies metamorphism at 1.5–2.1 GPa and 520–580°C. We explain co‐existence of eclogites and blueschists by compositional variation probably reflecting original compositional layering. It is also shown that the greenschists record retrogression at 0.34 ± 0.21 GPa and T = 456 ± 68°C. This was spatially associated with a shear zone on a scales of 10–100‐m and veins on a scale of 1–10‐cm. Greenschist facies metamorphism ended at (or shortly after) 27 Ma. We thus infer a period of metamorphic quiescence after eclogite/blueschist facies metamorphism and before greenschist facies retrogression which lasted up to 11–16 million years. We suggest that this reflects an absence of metamorphic fluid flow at that time and conclude that greenschist facies retrogression only occurred when and where metamorphic fluids were present. From a tectonic perspective, our findings are consistent with studies showing that the CBU is (a) a high‐ P nappe stack consisting of belts in which high‐ P metamorphism and exhumation occurred at different times and (b) affected by greenschist facies metamorphism during the Oligocene, prior to the onset of regional tectonic extension.